2019
DOI: 10.1039/c9sm00911f
|View full text |Cite
|
Sign up to set email alerts
|

On the blistering of thermo-sensitive hydrogel: the volume phase transition and mechanical instability

Abstract: This paper explores the physical mechanisms responsible for the appearance of small blisters on the surface of temperature sensitive hydrogels as they deswell rapidly during their volume phase transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…While these initial dynamics may be difficult to experimentally observe, our simulations show that these regions quickly coarsen and give rise to alternating zones of large and small compressive stress. In higher dimensions, this highly non-uniform stress distribution is likely to trigger instabilities leading to complex patterns as previously observed in experiments, for example, by Tanaka [3] and more recently by Shen et al [73] and Chang et al [74].…”
Section: Discussionsupporting
confidence: 52%
“…While these initial dynamics may be difficult to experimentally observe, our simulations show that these regions quickly coarsen and give rise to alternating zones of large and small compressive stress. In higher dimensions, this highly non-uniform stress distribution is likely to trigger instabilities leading to complex patterns as previously observed in experiments, for example, by Tanaka [3] and more recently by Shen et al [73] and Chang et al [74].…”
Section: Discussionsupporting
confidence: 52%
“…Temperature, light Mesogen-driven network deformation Oseen, 1933;Frank, 1958;Ericksen, 1961;Stephen and Straley, 1974;De Gennes and Prost, 1993;Terentjev, 1996, 2007;Finkelmann et al, 2001;Ikeda et al, 2007;Ohm et al, 2012;Jiang et al, 2013;White and Broer, 2015;Yakacki et al, 2015;Guin et al, 2018;McBride et al, 2018;Ula et al, 2018;Shang et al, 2019 Gels Hydrogels Humidity, other fluids Swelling-driven response Flory, 1950;Tanaka and Fillmore, 1979;Hong et al, 2008;Zhu et al, 2018;Agarwal et al, 2019 PNIPAm Humidity, other fluids, temperature change Temperaturedependent swelling-driven response Afroze et al, 2000;Yan and Tsujii, 2005;Deshmukh et al, 2013;Li et al, 2015;Vernerey and Shen, 2017;Işikver and Saraydin, 2019;Shen et al, 2019;Wang et al, 2020 PNIPAm, poly(N-isopropylacrylamide).…”
Section: Polymers With Conformational Instabilitiesmentioning
confidence: 99%
“…In these problems the fluid mass transport and the network deformation are coupled phenomena (Tanaka and Fillmore, 1979;Chirani et al, 2015). Gels have been employed also for developing smart and responsive materials to be used in flexible electronics, actuation, and soft robotics (Shen et al, 2017(Shen et al, , 2019Rong et al, 2018). For instance, hydrogels can mimic the pressure-driven trophic motion in plants and fungi and have been used to create light, humidity, or biological sensors capable of movement (Ionov, 2014).…”
Section: Swelling-driven Response Of Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments on these thermo-responsive gels have suggested that there is a difference between the behaviour of a homogeneous gel when swelling, compared to when shrinking: dynamic swelling has been observed to equilibrate exponentially, whereas the dynamics of a shrinking gel appears more complicated and can exhibit an instability that forms lobe-like structures (Sato Matsuo & Tanaka 1988). Temperature changes beyond transition have been observed to cause separation into distinct swollen and shrunken states along the length of a cylinder, with an appearance similar to the fluid-dynamical Rayleigh-Plateau instability (Matsuo & Tanaka 1992), as well as through the appearance of surface blisters that can cause deformation of rods and tori (Chang et al 2018;Shen et al 2019).…”
Section: Introductionmentioning
confidence: 99%